The Relationship between Nurses' Knowledge Level and Their Ability to Use Restrain in Patients with Violent Behavior - Bayu Seto Rindi Atmojo; Eko Riyanti; Ahmad Muzaki; Jayanti Indah Laila; Citra Ajeng Noorma Pratama (GLOBAL HEALTH SCIENCE GROUP, 2026)
Restraints applied to patients in mental hospitals also have negative impacts, the impact of restraints can occur on the patient themselves and the nurses who carry out this action. Therefore, in addition to knowledge, the ability of nurses to manage crisis situations is also very important. To determine the relationship between nurses' knowledge level and the use of restraints on patients with violent behavior at Prof. Dr. Soerojo Mental Hospital, Magelang. This study used an observational analytical approach using a cross-sectional approach. Sampling was conducted using a total sampling technique with a purposive sampling approach, involving 40 nurses. Data collection in this study used a questionnaire. Data were analyzed using the chi-square test. The The majority of respondents were aged 27-30 years (15 respondents) (37.5%), male (30 respondents) (75.0%), and 23 respondents (57.5%) had worked for 2-3 years. Most respondents had good knowledge (27 respondents) (67.5%). Most respondents used restraints moderately (26 respondents) (65.0%). Most respondents used restraints well (11 respondents) aged 17-25 years (27.5%). Most respondents used restraints well (13 respondents) (32.5%). There is a relationship between the level of nurses' knowledge and the use of restraint in patients with violent behavior at Prof. Dr. Soerojo Mental Hospital, Magelang.